Cognitive Macro knowledge: A Semantic View of Translating Meanings of the Qur’anic Texts - Mohammed Nihad Ahmed (PROSPECTIVE RESEARCHES, 2023)
The major goal of this paper is to focus on the necessity of macro knowledge in translating process. It is hypothesized that macro knowledge constituents include conceptual components within the mental model that constitutes knowledge clusters as a major part of the cognitive system in general. This paper demonstrates the conceptual components underlying the formation of new mental images in exegeses of Qur'anic text on the one hand, and the translating process on the other, which agrees with the idea that says that translation is complex bilingual mediated communication. The macro knowledge is posited in this process with inference making mechanisms in mental model. As Qur'anic text is characterized by a high level genre that contains multifarious types of figurative tropes, the translator transfers the semantic and logical connectivity, mental image (conceptual structures), aesthetic standards and emotional charge of SL into TL keeping the norms of both languages as well as keeping the accuracy, fidelity and sanctity of the glorious Qur'anic text. The current study concludes that translation is a pure cognitive bilingual process in terms of macro knowledge constituents, and has a major operation performed in terms of knowledge and inference within the mental model.